2003
DOI: 10.1097/01.ccm.0000049947.80131.ed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adverse drug reactions on length of stay in surgical intensive care units

Abstract: Adverse drug reactions are a significant clinical and economic problem in surgical intensive care units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 37 publications
1
35
1
2
Order By: Relevance
“…There are several stages in the medication process, from the supply of drugs and their storage in the clinical area to drug prescription, preparation, administration and monitoring the response to treatment. The multiple risks in each of these stages have resulted in many reports of medicationrelated harm or potential harm to critically ill patients [1][2][3][4][5][6][7]. In one of these studies [5], medication errors accounted for over 60% of all reported adverse incidents in critical care, while in another study almost 10% of patients in intensive care suffered an adverse drug event [7].…”
Section: Discussionmentioning
confidence: 99%
“…There are several stages in the medication process, from the supply of drugs and their storage in the clinical area to drug prescription, preparation, administration and monitoring the response to treatment. The multiple risks in each of these stages have resulted in many reports of medicationrelated harm or potential harm to critically ill patients [1][2][3][4][5][6][7]. In one of these studies [5], medication errors accounted for over 60% of all reported adverse incidents in critical care, while in another study almost 10% of patients in intensive care suffered an adverse drug event [7].…”
Section: Discussionmentioning
confidence: 99%
“…The cost-generating components were decided based on published literature [8,[18][19][20][21], and the researchers' conservative estimates. Monetary values for the components were determined from national statistics [22][23][24] and personal communications with register holders [Gyllensten H. Personal communication] on costs of healthcare and drug utilisation.…”
Section: Cost-of-illness Analysesmentioning
confidence: 99%
“…Although no adverse drug reactions with the antifungal agents were documented in this study, underrecognition and underreporting of adverse drug reactions common (1,(5)(6)(7)12). In fact, adverse drug reactions are recognized as being present in at least 6% of hospitalized patients and have been documented as causing increased lengths of stay (12,13,19). Fluconazole and ketoconazole have similar mechanisms of action, and so they share similar drug-drug interactions (R. Polk, Program Abstr.…”
Section: Vol 41 2003 Benefits Of Limited Yeast Id In Respiratory Sementioning
confidence: 99%